Relações entre território e educação na comunidade quilombola de Vila Santo Isidoro - Berilo/MG - Tatiane Campos dos Santos (2015)
In this research, we have investigated the role of School and the construction of Identity in Vila Santo Isidoro Maroons community, located in Berilo, Jequitinhonha Valley/ Minas Gerais, in the perspective of Cultural Geography/ Ethnogeography. Some educational activities developed in the community were analysed in this sense. The methodological tools adopted for the development of this study included: bibliographic and documentary research; field works; cross walk; carrying out semi-structured interviews and development of mental maps. It was concluded Santo Isidoro State School, inserted in the community, is an instrument with the potential to legitimize the identity aspects of the group studied. It should be noted that the School was a result of the struggle of a community's own resident and so, it has the specificity of being in the community and being of the community; and, as a consequence, the actions taken there result of a collective effort to enhance the group's everyday life